If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2u+3=9u+10
We move all terms to the left:
2u+3-(9u+10)=0
We get rid of parentheses
2u-9u-10+3=0
We add all the numbers together, and all the variables
-7u-7=0
We move all terms containing u to the left, all other terms to the right
-7u=7
u=7/-7
u=-1
| 4z+3=7z-9 | | -(6x+3)=-(6x+40 | | 9s=–9 | | -(6x+3)=-(6x+4+ | | -15/7=-3x | | 3v=3v+5 | | 3(z-8)=9 | | a*3=3.1 | | -10+4r=10+9r | | 5x+2=2x+42 | | 38=r+21 | | (d-2)/(d+9)=3/14 | | 8x−5=7x+13 | | 2+512x=12+314x | | 3m-72=12 | | 2=3f+15 | | 3n=n+2n | | -7+x=(7+x) | | 2n+6.1=18.3 | | 2x+314x=12x+512x | | 4(10-x)=40-4x | | x/4(1-x)/5=3 | | 8f-9f=-9+f | | 2x+314x=12x+512x | | 6x+2x+3=40 | | (2x+1)(x-2)=-2 | | c=8=9 | | 27=w+7 | | 2x-5=x+3=90 | | 6.7+b=4b+4 | | 2.3x+7=-7 | | c=9=8 |